ABOLITION OF ARTICLE ON THE HEAD OF THE CORRUPTION ERADICATION COMMISSION AS INVESTIGATOR AND PUBLIC PROSECUTOR IN THE LAW ON THE CORRUPTION ERADICATION COMMISSION - Abdul Kadir (Jurnal Hukum Replik, 2021)
The revision of the Corruption Crime Act is part of the government's legal politics in carrying out reforms to eradicate corruption in Indonesia. The authority of the KPK leadership as an investigator and the public prosecutor has been abolished in the latest regulation. The issues raised in this journal are How the Development of Amendments to the Corruption Eradication Commission Law and How the Legal Politics of the Elimination of Articles of KPK Leaders are Investigators and Public Prosecutors in the Revision of the Law on the Corruption Eradication Commission. The research used in this journal uses normative research methods. The development of Amendments to the Corruption Eradication Commission Law in Indonesian Legal Politics was marked by several changes to the Law, including Law Number 30 of 2002, Law Number 10 of 2015 concerning Stipulation of Government Regulations in Lieu of Law Number 1 the Year 2015, and Law Number 19 of 2019 concerning the Corruption Eradication Commission. The position of the KPK leadership must be understood wisely and completely, do not interpret it partially so that the KPK leadership remains authorized to carry out investigations and prosecutions. Keywords: Article Abolition, KPK Leaders, Investigators, Public Prosecutors